2020
DOI: 10.1108/mbe-10-2018-0080
|View full text |Cite
|
Sign up to set email alerts
|

A template-based approach to measure supply chain flexibility: a case study of Indian soap manufacturing firm

Abstract: Purpose The purpose of this study is to quantify the supply chain flexibility for an Indian soap manufacturing firm and to measure its performance. The authors made an attempt to find key strategic and operational decision-making dimensions for developing effective supply chain flexibility environment. Design/methodology/approach The authors have extracted 11 supply chain flexibility dimensions through extensive literature review. The authors used a decision-making trial and evaluation laboratory (DEMATEL) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 75 publications
2
48
0
Order By: Relevance
“…In addition, causality and barrier interactions have been established as a potential future research direction. One approach that defines both qualitative and causal relationships is DEMATEL (Raj et al , 2020; Singh et al , 2019, 2020b; Sharma et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, causality and barrier interactions have been established as a potential future research direction. One approach that defines both qualitative and causal relationships is DEMATEL (Raj et al , 2020; Singh et al , 2019, 2020b; Sharma et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, the result of ( r i − c j ) on the system represents the net contribution from barrier i (Sharma et al , 2020; Singh and Acharya, 2014). In addition, if ( r i − c j ) is positive, barrier i is a net cause and if negative, barrier i is a net effect (Singh et al , 2020b; Lee et al , 2009; Yang et al , 2008). Table 6 outlines the degree of total influence of Industry 4.0 barriers.Step 6: The threshold value ( α ) has been determined using equation (5) as the average of the elements in matrix ( T ).…”
Section: Dematel Analysis For Industry 40mentioning
confidence: 99%
“…Consistent with the indicated premise, information sharing according to Colicchia et al (2018) is the glue that holds supply chains together especially with regards to supply chain partners. Singh et al (2020) further indicated that miscommunications, which result from poor information sharing, creates conflicts and misunderstandings in supply chains, which defeat the overall goal of superior performance. Cao and Zhang (2011) recommended that information sharing is a critical component of supply chain collaborations and as such, collaborations between supply chain partners can be based on leveraging information sharing to acquire competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…(16) (17) (18) (19) Equations ( 16) to (19) show restrictions on transportation. Equation ( 16) describes conditions upon transportation to end-users from plants.…”
Section: Number Of Component C Generated In Machine M In Time Tmentioning
confidence: 99%
“…Equation ( 18) reveals restrictions on transportation to end-users from warehouses. Equation (19) shows restrictions on transportation capacity. (20)…”
Section: Number Of Component C Generated In Machine M In Time Tmentioning
confidence: 99%